Family member deaths across adulthood predict Alzheimer's disease risk: The Cache County Study. (1st July 2015) - Norton, Maria C.; Fauth, Elizabeth; Clark, Christine J.; Hatch, Dan; Greene, Daylee; Pfister, Roxane; Tschanz, JoAnn T.; Smith, Ken R.
Abstract : Objectives: Parental death during childhood, and offspring and spouse death during adulthood have individually been associated with faster cognitive decline and higher Alzheimer's disease (AD) risk in late life. However, the cumulative effect of childhood and adulthood family deaths on AD risk among different age cohorts has not been studied. Methods: To examine these associations, this prospective cohort study uses a population‐based sample of 4545 initially non‐demented participants (56.7% female; age M = 75.0/SD = 6.9 years) observed at four triennial waves, linked with objective Utah Population Database data on cumulative mother, father, sibling, spouse, and offspring death experienced during childhood and adulthood. Cox regression modeled survival time from baseline interview to AD onset, as a function of family deaths during childhood or adulthood, among different age groups, along with gender and presence of ε4 allele at apolipoprotein E (APOE) polymorphic genetic locus. Results: Age group significantly moderated the relationship between family death and AD; among persons aged 65–69 years at baseline (children of the Great Depression), those exposed to 3–4 deaths and 5+ deaths during adulthood exhibited a doubling of AD risk (adjusted hazard ratio, aHR = 2.25, p  = .038, and aHR = 2.72, p  = .029), while among persons aged 80 years and older, those exposed to 3–4 deaths during adulthood exhibited lower AD risk (HR = 0.539, p  = 0.014). In a combined model of childhood and adulthood deaths, these findings persisted. Conclusions: Results suggest a cohort effect in the link between family member deaths during adulthood and AD risk later in life. Copyright © 2015 John Wiley & Sons, Ltd.